The Impact of Climatic Changes on Forage Pea (Pisum sativum var. arvense) Production - Maho, Adrian; Biturku, Jonida; Maho, Ferdinant (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
The yield of agricultural crops is significantly influenced by climatic factors. This impact has been intensified as a result of rapid changes in agroclimatic indicators. These factors are constantly changing. Climate indicators such as temperature, precipitation amount and distribution, snowfall amount and duration, have shown significant changes over the past decades. The sustainability of agricultural farms can only be positive by treating them as sustainable agroecosystems. Technologies and agricultural practices need to be harmonized with ongoing climate changes. The study is based on a multi-year analysis of climatic indicators in the Korça region, examining the impact of these changes on morphological, physiological, and production of the forage pea "Voskopoja." Climatic changes was reflected in significant changes in green mass yield, seed numbers per pod and seed weight per pod (g) and seed yield. Climatic changes was not reflected in significant changes in the number of pods per plant and the weight of 1,000 seeds. Climate change showed significant effects on seed protein content and protein yield. Prcentage of protein content in seeds was higher in the year with the lowest amount of rainfall and the highest temperature of the April-June period. Protein yield (kg/ha) was the highest in the year with the greatest amount of rainfall and the lowest temperature of the April-June period. The experimental conclusions are based on the statistical analysis of variance between different climatic indicators and productivity.